Exploring How Lecturers Comprehend and Apply Critical Pedagogy in English Listening Class - Rokhaniyah, Hesti; Nuraini, Eka Indah; Sa-a, Firdaus (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
Grounded in Freire’s (1971) critical pedagogy premise revealing that the act of listening should be active, critical, and transformative, rather than passive or merely receptive, this research explored the experience of English language lecturers who taught English listening classes with a critical pedagogy approach. This study employed a qualitative method through a case study design to explore lecturers' understanding in depth and their practices of critical pedagogy. Data were collected through in-depth interviews with four lecturers and analyzed using Braun and Clarke’s (2006) thematic analysis. The analysis identified key themes in lecturers' understanding, including their awareness of the transformative potential of listening activities, the importance of fostering student autonomy, and their understanding of listening as a dialogic process. The findings also indicate that while lecturers did not explicitly define or describe critical pedagogy, certain stages and elements of it were evident in their teaching. In practice, lecturers applied the principles of critical pedagogy by providing authentic materials, building horizontal relationships, developing critical consciousness, encouraging critical, democratic, and participatory assessment to support transformative learning, while contending with challenges like low student engagement, language proficiency, and diverse accents. This suggests that, to some extent, they incorporated aspects of critical pedagogy in their listening classes. The practical implications of this research recommend that lecturers should receive targeted training in critical pedagogy to better align their teaching practices with its principles, while institutions should provide resources and support to address the challenges.